"Belale" Local Culture through Ritual Procession to Sambas Malays Society - Fatmawati,; Rahmaniah, Syarifah Ema; Hayat, (International Journal of Psychosocial Rehabilitation, 2020)
Local Culture of Belale through ritual procession in the Sambas Malay society as the tradition activity of cultivation of agricultural land which is carried out cooperatively and is done once in a year during the growing session. The purpose of this paper is to study about the local culture of Belale at the time of cultivation of agricultural land accompanied by a ritual procession. This research uses a qualitative method with the descriptive type of research, that is describing the ritual procession of Belale in Sambas Malay society. Data collection techniques using observation techniques, in-depth interview of the context of the Belale ritual procession. The data sources of this research were informants from Malay ethnic who carried out agricultural activities, traditional leaders, and Society Leaders, while the data analysis uses qualitative analysis by describing elaborately about Belale local culture in the Sambas Malay society. The results of the research explained the activities of cultivating agricultural land are carried out in stages starting from the stage of land preparation, the icamai stage (sow), nandor stages (planting rice), beranyi stages (rice harvest), and the stages of eating new rice. All stages are accompanied by a ritual procession asking for blessing and a sign of gratitude to God who has given a fortune to humans. Changes occur as the development of modernization regarding the belale ritual procession if ancient times reciting prayers asking supernatural beings accompanied by food offerings given to supernatural beings, while now the essence of the belale is to do the belale procession through the reading of prayers only to God, not to supernatural beings.